2011
DOI: 10.1186/1477-5751-10-6
|View full text |Cite
|
Sign up to set email alerts
|

No connection between the level of exposition to statins in the population and the incidence/mortality of acute myocardial infarction: An ecological study based on Sweden's municipalities

Abstract: BackgroundRandomised controlled trials have shown an excellent preventive effect of statins on ischemic heart disease. Our objective was to investigate if a relation can be detected between acute myocardial infarction- (AMI) mortality or incidence and statin utilisation, for men and women in different age-groups on a population basis.ResultsThe utilisation rate of statins increased almost three times for both men and women between 1998 and 2002. During 1998-2000 the incidence of AMI decreased clearly for men b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This was confirmed in a Swedish study including a large sample of municipalities, where no correlation was shown between statin utilisation and acute myocardial infarction incidence or mortality. 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was confirmed in a Swedish study including a large sample of municipalities, where no correlation was shown between statin utilisation and acute myocardial infarction incidence or mortality. 31 …”
Section: Discussionmentioning
confidence: 99%
“… 54–56 Higher prescription rates have been reported in women and the elderly. 31 57 There is also a socioeconomic gradient in the utilisation of statins. More patients with higher income and educational levels start statin treatment compared to patients with lower income, especially in secondary prevention.…”
Section: Discussionmentioning
confidence: 99%
“…However, this interpretation is highly questionable [72]. In a Swedish study including 289 of the 290 municipalities, no association was found between statin use and the change in mortality from AMI [102]. Also, the American National Health and Nutrition Examination Survey [103] found that during the period 1999-2006, the number of AMI and strokes increased from 3.4% to 3.7% and from 2.0% to 2.9%, respectively.…”
Section: Has Cvd Mortality Decreased After the Introduction Of Statinmentioning
confidence: 98%
“…По-прежнему заболевания атеросклеротической природы остаются наиболее распространенными и занимают первые строчки в списке причин смерти. Предположение о том, что снижение сердечно-сосудистой смертности, отмечаемое в последние десятилетия в некоторых странах, может быть связано с массовым применением гиполипидемических средств (статинов), встречает серьезные возражения [1][2][3].…”
Section: Introductionunclassified